Diagnostic Dilemma: Acute Abdomen from Ruptured Corpus Luteum Requiring Surgical Intervention in Young Women - Yoke Fai Fong; Hui Wen Chua; Chanchal Singh (The Royal Thai College of Obstetricians and Gynaecologists, 2013)
Aim:Rupture of corpus luteum can occur in women of reproductive age, and is usually asymptomatic. Rarely, there is hemoperitoneum leading to circulatory shock requiring surgical intervention. This presents a diagnostic dilemma, with differential diagnoses of appendicitis, ectopic pregnancy and torsion of adnexal mass to consider. This study was undertaken to define characteristics and risk factors for corpus luteum rupture, to improve diagnostic capability and optimize management. There is a lack of local data on the incidence, and we hope to provide updates on management, given the ubiquity of laparoscopic surgery now. Materials and Methods:A retrospective study was conducted on patients treated surgically for ruptured corpus luteum at National University Hospital, Singapore, from September 1, 2004 to March 31, 2011, looking at demographics, clinical features, operative findings and follow-up. Results: 47 cases were analyzed; 80.8% in peak reproductive age of 15-34 years, 25.5% in first trimester pregnancy. Most are healthy, but two patients were newly diagnosed with idiopathic thrombocytopenic purpura on this admission. All patients presented with severe abdominal pain, while some also had signs of peritoneal irritation. 55.4% of such patients were initially misdiagnosed. Sonography revealed free fluid in 84.1%. Diagnostic laparoscopies were performed in 78.7%; with the rest undergoing laparotomies. Hemoperitoneum below 1L was seen in 85.1% of patients, above 1L in seven patients, of which three went onto require blood transfusions. All patients recovered well, with return of normal menses. None of the patients required further surgical treatment. Conclusion: Increasing awareness of ruptured corpus luteum is recommended, especially for cases with right-sided pain, pregnancy and adnexal masses. High index of suspicion is required for timely intervention for securing hemostasis. Laparoscopy is used first-line, except cases better managed by laparotomy. Underlying bleeding diatheses can be a predisposing factor. Recurrence may be prevented with ovulation suppression.